2011
DOI: 10.1002/sia.3451
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of organic multilayered samples for optoelectronic devices by (low‐energy) dynamic SIMS

Abstract: aThe increasing sophistication of optoelectronic devices requires molecular-level dimensional control in the fabrication of multilayered structures with specifically engineered interfaces. However, the effectiveness of growth and doping strategies devised to achieve the desired device structures often remains unverified due to the lack of adequate characterization techniques. This is particularly true for devices based on conjugated organic compounds, which find increasing use in energy applications (e.g. orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…SIMS has been employed in a number of OPV [259][260][261][262][263][264][265] and hybrid PV 266 morphology experiments. Krebs et al have reported extensively on the analysis of degradation mechanisms in OPVs, which were among the first studies to clearly demonstrate that oxygen and water enter devices via diffusion from the atmosphere through the top (aluminum) electrode.…”
Section: Additional Techniquesmentioning
confidence: 99%
“…SIMS has been employed in a number of OPV [259][260][261][262][263][264][265] and hybrid PV 266 morphology experiments. Krebs et al have reported extensively on the analysis of degradation mechanisms in OPVs, which were among the first studies to clearly demonstrate that oxygen and water enter devices via diffusion from the atmosphere through the top (aluminum) electrode.…”
Section: Additional Techniquesmentioning
confidence: 99%
“…Under low-energy Cs + bombardment, the fragmentation is less prevalent than for kiloelectronvolt bombardment, 13,14 and stable secondary ion intensities of small characteristic fragments are obtained under steady-state conditions. 15 The successful depth profiling of metal−organic multilayered samples 16 and the ability to extract information on the interface morphology 17 have been reported previously. This includes the control of roughness formation for the experimental conditions used 18,19 and of Cs−O nanodot formation in the areas irradiated by a Cs + primary ion beam 20 due to the high mobility of cesium.…”
Section: ■ Introductionmentioning
confidence: 82%
“…21 Depth profiles presented in previous work also show high Ag secondary ion intensities inside the organic layer. 16,17 Other authors have already encountered this problem. Fostiropoulos et al investigated the metal diffusion into organic films by SIMS by comparing the depth profiles from an Ag/Mg/CuPc:C 60 device with and without lifting off the Ag/Mg cathode.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, MD simulations are able to provide information which is complementary to the experimental results obtained in our group on the enhancement of secondary ion emission under Cs + 0168-583X/$ -see front matter Ó 2010 Elsevier B.V. All rights reserved. doi:10.1016/j.nimb.2010.12.059 bombardment combined with simultaneous Cs 0 deposition [23][24][25][26] or the fragmentation of organic molecules [27,28]. For the MD simulations, we will use the force field developed by Kieffer et al which has already been applied successfully, for example, to the study of phase transitions in cristobalite [1,[29][30][31] and B 2 O 3 [2,32].…”
Section: Introductionmentioning
confidence: 99%